Investment pattern and costs and return structure of rice mills in sultanpur district of uttar pradesh - P. RADHIKA, SAURABH SINGH, SEEMA and (The Journal of Research, PJTSAU, 2017)
Rice (Oryza sativa L.) is the basic grain consumed as a food in India which is found in almost every Indian kitchen. It is the most common grain and the most common food in India. However, India is not only a big consumer of rice but also it is the second largest producer of rice in the world after China. India also holds the largest agriculture land for paddy production in the world. In the total arable land for paddy in the world was 165 million hectares with the total production of 721.4 million tonnes of paddy, out of which 44 million hectares of the area was held by India alone, which produced 104 million tonnes of paddy just second after 200.7 million tonnes by China.